2015
DOI: 10.1002/lary.25748
|View full text |Cite
|
Sign up to set email alerts
|

Internal carotid artery injury in endoscopic endonasal surgery: A systematic review

Abstract: NA Laryngoscope, 126:582-590, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
126
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(126 citation statements)
references
References 46 publications
(104 reference statements)
0
126
0
Order By: Relevance
“…ICA injury is the most catastrophic complication of EEA and in-depth anatomic knowledge and proper surgical technique are paramount to prevent it. The most commonly injured ICA segment was the cavernous, followed by the ophthalmic; this could occur at various surgical steps3). ICA injuries can sometimes be repaired but often require nasal packing and endovascular sacrifice3,9,20).…”
Section: Complications and Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICA injury is the most catastrophic complication of EEA and in-depth anatomic knowledge and proper surgical technique are paramount to prevent it. The most commonly injured ICA segment was the cavernous, followed by the ophthalmic; this could occur at various surgical steps3). ICA injuries can sometimes be repaired but often require nasal packing and endovascular sacrifice3,9,20).…”
Section: Complications and Preventionmentioning
confidence: 99%
“…The most commonly injured ICA segment was the cavernous, followed by the ophthalmic; this could occur at various surgical steps3). ICA injuries can sometimes be repaired but often require nasal packing and endovascular sacrifice3,9,20). Valentine et al performed animal model experiments to compare the efficacy of packed material in ICA injury.…”
Section: Complications and Preventionmentioning
confidence: 99%
“…1,5 The complex anatomy of the head and neck region and the proximity of multiple vital structures make most surgical interventions carry an inherent risk of accidental injury of nearby structures, such as the facial nerve, recurrent laryngeal nerve, thoracic duct, salivary duct, sigmoid sinus, tegmen, jugular bulb, and carotid artery. [6][7][8][9][10][11] No previous study has addressed the overall prevalence of such injuries in otolaryngology practice at the national level. The purpose of this study was to provide a general perspective on accidental intraoperative injury of nearby structures reported in head and neck surgeries in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…As endoscopic endonasal surgery (EES) of the anterior cranial base increases in frequency, the number of iatrogenic cranial base pseudoaneurysms may also be increasing . Although it is difficult to discern the exact incidence of cranial base pseudoaneurysms, a recent review suggested that at least 20% of patients undergoing EES with intraoperative arterial injury develop delayed pseudoaneurysms . Similarly, as surgical techniques continue to advance, the role of EES in the management of pseudoaneurysms is evolving.…”
mentioning
confidence: 99%
“…Similarly, as surgical techniques continue to advance, the role of EES in the management of pseudoaneurysms is evolving. Numerous publications have discussed the acute management of ICA injury during EES and the endoscopic management of true aneurysms . However, there is a dearth of knowledge regarding the presentation and management of nontraumatic cranial base pseudoaneurysms, which present unique diagnostic and treatment dilemmas.…”
mentioning
confidence: 99%